Investigating oral microbiome profiles in patients with cleft lip and palate compared with the healthy control - Wenxiu Jiang; Zixin Yan; Zhenwei Chen; Lanxin Gu; Han Bao; Ye Cao; Luwei Liu; Bin Yan (BMC Oral Health, 2024)
Abstract Background Patients with cleft lip and palate (CLP) have an oronasal communication differed from the closed state in healthy individuals, leading to a unique oral microbiome. This study aimed to determine if variances in the oral microbiota persist among CLP patients who have received treatments for the closure of these fistulas compared to the microbiota of healthy individuals. Methods Saliva samples were collected from a cohort comprising 28 CLP patients (CLP group) and 30 healthy controls (HC group). Utilizing 16S rRNA sequencing on the Illumina NovaSeq platform, we conducted a comprehensive analysis of the diversity and composition of the oral microbiota. Results The analysis of the microbiota in the saliva samples revealed a total of 23 microbial phyla, 38 classes, 111 orders, 184 families, 327 genera and 612 species. The alpha diversity with microbial abundance and evenness indicated the significant difference between the CLP and HC groups. Principal coordinate analysis (PCoA) and the ADONIS test further supported the presence of distinct microorganisms between the two groups. The CLP group displayed elevated abundances of Neisseria, Haemophilus, Porphyromonas, and Granulicatella, as indicated by LefSe analysis. Conversely, Rothia, Veillonella, and Pauljensenia exhibited significant reductions in abundance in the CLP group. The results of the PICRUSt analysis indicated significant differences in the relative abundance of 25 KEGG pathways within the CLP group. Through Spearman correlation analysis, strong associations between Rothia, Veillonella, and Pauljensenia and 25 functional pathways linked to CLP were identified. Conclusion Findings of this study offer a thorough comprehension of the microbiome profiles of CLP patients after the restoration of oronasal structure and are anticipated to present innovative concepts for the treatment of CLP.